Regional differences in prescription of drugs with proven efficacy in reduction of mortality in secondary prevention of cardiovascular events - Pietrasik, Arkadiusz; Starczewska, Marta E.; Główczyńska, Renata; Filipiak, Krzysztof J.; Łatek, Maciej; Opolski, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2005)
Current paper describes regional differences in prescription of drugs, with proven efficacy in reduction of mortality, in secondary prevention of cardiovascular diseases. Data were gathered alongside POLKARD-SPOK survey, which was performed, under the auspices of the Ministry of Health in Poland, to distinguish risk factors and describe their management in relation to current guidelines in prevention of cardiovascular diseases, in primary care practice. POLKARD-SPOK reveled significant regional differences in frequency of prescribed drugs such as aspirin, beta-blockers, ACE inhibitors and statins in primary care settings. In accordance to present secondary prevention guidelines usage of these drugs remains insufficient.